2013
DOI: 10.1007/s12199-013-0328-8
|View full text |Cite
|
Sign up to set email alerts
|

Developmental origins of obesity and type 2 diabetes: molecular aspects and role of chemicals

Abstract: Obesity is a leading risk factor for impaired glucose tolerance and type 2 diabetes (T2D). Although the cause of the obesity epidemic is multi-factorial and not entirely clear, the recent acceleration in incidence is too rapid to be accounted for only by genetics, the wide availability of calorie-rich foods, and increasingly sedentary lifestyles. Accumulating data suggest that the important causes of the obesity epidemic may be related to developmental and early life environmental conditions. The concept of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 167 publications
(127 reference statements)
2
74
0
Order By: Relevance
“…There is increasing experimental and epidemiological evidence that T2D and obesity, which is an important risk factor for T2D, may originate during critical windows of prenatal and early postnatal development [2]. These findings are consistent with the developmental programming of health and disease (DOHAD) hypothesis which proposes that physiology and structure of the developing fetus may be adapted in response to adverse developmental conditions, such as poor nutrition, predisposing to various pathological conditions later in life [3]. In the case of T2D, fetus likely can be adapted to poor nutritional environment in a way to reduce capacity to produce insulin and increase insulin resistance thus providing short-term survival benefit but predisposing to the development of T2D in conditions of postnatal food abundance.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…There is increasing experimental and epidemiological evidence that T2D and obesity, which is an important risk factor for T2D, may originate during critical windows of prenatal and early postnatal development [2]. These findings are consistent with the developmental programming of health and disease (DOHAD) hypothesis which proposes that physiology and structure of the developing fetus may be adapted in response to adverse developmental conditions, such as poor nutrition, predisposing to various pathological conditions later in life [3]. In the case of T2D, fetus likely can be adapted to poor nutritional environment in a way to reduce capacity to produce insulin and increase insulin resistance thus providing short-term survival benefit but predisposing to the development of T2D in conditions of postnatal food abundance.…”
Section: Introductionsupporting
confidence: 66%
“…Maternal malnutrition and gestational diabetes were shown to be the most important contributors to obesity and metabolic dysfunction in offspring [3]. A relation between birth weight, which is an indicator of fetal growth, and later-life risk of T2D was shown to be not linear but rather U-shaped, and high birth weight is associated with an increased risk of T2D to the same extent as low birth weight [4].…”
Section: Introductionmentioning
confidence: 99%
“…38) Indeed, even transient imbalances in maternal nutrition during fetal development can trigger heritable epigenetic disturbances, such as abnormal placental DNA methylation and histone modifications, and subsequent risks of adult obesity and diabetes. [39][40][41] The "developmental origin of health and disease (DOHaD)" hypothesis proposed by Barker et al recognizes that maternal eating disorders during pregnancy can lead to adverse consequences in offspring. [42][43][44] Based on reports indicating that intrauterine leptin conditions contribute to DOHaD, 38,45,46) it can be said that the control of the mater-nal Zn nutrition may be critical.…”
Section: Discussionmentioning
confidence: 99%
“…21,24,25 It has been suggested that babies who experience growth restriction in utero and therefore are born small compensate by growing rapidly in early infancy, and that this mismatch between prenatal and postnatal growth may elevate risks of obesity and other chronic diseases. [26][27][28] If this is the case, there could be trade-offs between the short-term benefits of 'catch-up' growth and chronic disease risk in the longer-term.…”
Section: Introductionmentioning
confidence: 99%